A study of hygiene and sanitation among migrants reporting to a primary health care setting in North Goa - Mendes, Jennifer; Shah, Hemangini K. (International Journal Of Community Medicine And Public Health, 2019)
Background: Considering that poor hygiene and inadequate sanitation has always been a major public health challenge and is responsible for the increased burden of communicable diseases in developing countries, and also the migrant population being a vulnerable community, the present study has been undertaken to evaluate this issue among them. Methods: A cross sectional study was conducted at a primary healthcare setting, wherein migrant population reporting to the centre were assessed for knowledge, attitude and practices regarding personal hygiene and sanitation. Also, the prevalence of hygiene and sanitation associated communicable diseases was assessed based on history and clinical examination to check for the same. Results: The study revealed that most of the study participants used a shared/community latrine (86%), followed by single household latrine (10%) and 4% participants practiced open defecation. During post defecation handwashing, 42% used water and soap every time, 39% used water and soap sometimes and 19% used water only. The most commonly reported poor hygiene and sanitation associated illness was acute gastro-enteritis (52%), followed by respiratory tract infections (39%), taenia (22%), genitor-urinary infections (12%) and others such as eye infections, dental caries, etc. (15%). 85% practice sanitary disposal of solid and liquid waste and 15% dumped the waste at a dump site or into the gutter. Conclusions: From this study, we can conclude that there is inadequate knowledge regarding good hygiene and sanitation practices, and also that considerable proportion of the study population follow unhygienic and unsanitary practices.